2017
DOI: 10.1016/j.cmi.2017.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Rapid detection of Group B streptococcus directly from vaginal–rectal specimens using liquid swabs and the BD Max GBS assay

Abstract: The BD Max GBS assay is highly sensitive, requires minimal technical skill with <2 min required to set-up, and results are available in under 80 min (versus 24-48 h for culture). It is configured for 'on demand' testing and vaginal-rectal specimens can be rapidly screened for GBS without the need for enrichment. The results obtained in this study demonstrate that rapid GBS screening using the BD Max GBS assay at the time of delivery is a viable alternative to the current recommended screening at 35-37 weeks of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
(17 reference statements)
0
9
1
Order By: Relevance
“…Recently, Ellem et al . also demonstrated that the direct BD Max GBS assay offered viable alternative to the current CDC recommended screening culture‐based method, but they detected one more GBS isolates by enrichment culture than direct BD Max assay unlike that found in the present study …”
Section: Discussioncontrasting
confidence: 80%
“…Recently, Ellem et al . also demonstrated that the direct BD Max GBS assay offered viable alternative to the current CDC recommended screening culture‐based method, but they detected one more GBS isolates by enrichment culture than direct BD Max assay unlike that found in the present study …”
Section: Discussioncontrasting
confidence: 80%
“…It was found that the rapid GBS screening using the BD Max GBS assay, even at the time of delivery, is a viable alternative to the current recommended screening procedures at 35e37 weeks of gestation with pre-enrichment testing methods. Moreover, Ellem et al claim that the vaginalerectal specimen can be rapidly screened for GBS presence, directly after collection, without the need for its enrichment, reaching the sensitivity of 98.4%, compared to 100% sensitivity when it followed the broth enrichment culture [6].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the discrepancy analysis seems to indicate that both PCR assays were affected by freeze-thawing because some of the BD MAX samples that were initially positive, changed status to negative despite a high number of GBS-colony-forming units in the samples, based on the semi-quantitative culture results. It is also relevant to note that, in a recent clinical study using fresh vaginal-rectal swab specimens, the BD MAX GBS PCR assay detected 61 specimens with and 62 without enrichment culture, respectively, among 62 culture-positive specimens[13].…”
Section: Discussionmentioning
confidence: 99%
“…The difference in run time between the BD MAX and GenomEra PCR assays is only one hour (120 minutes vs. 60 minutes, respectively). Notably, the BD GeneOhm StrepB assay is a rapid and sensitive PCR assay (~ 1 hour) [13]. However, for optimal performance, the BD system still requires specially trained laboratory staff.…”
Section: Discussionmentioning
confidence: 99%